Analysis of fentanyl analogs and novel synthetic opioids in blood, serum/plasma, and urine in forensic casework. Issue 9 (3rd May 2018) - Moody, Marykathryn Tynon; Diaz, Stephanie; Shah, Parul; Papsun, Donna; Logan, Barry K.
Abstract: In recent years an increasing number of novel opioids have appeared on the illicit drug market and have been linked to the growing opioid crisis in the United States. It is suspected that synthetic‐opioid‐related deaths are underestimated since many laboratories either use a screening method that is not specific and sensitive enough for these compounds or testing is not performed for fentanyl and its related analogs in general. We describe a method for the analysis of 19 of the most current novel opioid drugs quantitatively in whole blood and serum, and 17 analytes qualitatively in urine using solid phase extraction with liquid chromatography–tandem mass spectrometry (LC–MS/MS). The limit of detection was determined to be at a minimum 0.25 ng/mL for beta‐hydroxythiofentanyl, 0.05 ng/mL for butyryl/isobutyrylfentanyl, AH‐7921, 2‐furanylfentanyl, 4‐ANPP, and U‐47700; 0.025 ng/mL for MT‐45, para‐methoxybutyrylfentanyl, 4‐methylphenethyl acetyl fentanyl, U‐50488, acrylfentanyl, valerylfentanyl, and carfentanil; and 0.0125 ng/mL for para‐fluorofentanyl, ortho‐fluorofentanyl, para‐fluorobutyrylfentanyl/FIBF, and alpha‐methylfentanyl. The lower limit of quantitation was determined to be 0.1 ng/mL for all analytes except AH‐7921, U‐47700, U‐50488 which were 0.05 ng/mL and beta‐hydroxythiofentanyl which was 0.5 ng/mL. The method was validated successfully according to a Scientific Working Group in Forensic Toxicology (SWGTOX) compliant approach. This method was applied to the analysis of 2758 samples between October 2016 and September 2017. It was determined that 4‐ANPP, furanylfentanyl, and carfentanil were the 3 most prevalent fentanyl related compounds detected: 56.1% of cases were positive for 4‐ANPP, 44.5% were positive for furanylfentanyl, and 25.2% cases were positive for carfentanil. Abstract : In recent years increasing number of novel opioids have appeared of the illicit drug market and have been linked to the growing opioid crisis in the United States. We describe a method for the analysis of 19 of the most current novel opioid drugs quantitatively in whole blood and serum, and 17 analytes quantitatively in urine using solid phase extraction with liquid chromatography tandem mass spectrometry (LCMS/MS).